Vortex Distribution and Energy Loss in S-Shaped Region of Pump Turbine - Zeng, Hongji; Li, Zhenggui; Li, Deyou; Chen, Hao; Li, Zhihong (Frontiers in Energy Research, 2022)
Research on the S-shaped region of pump turbines requires a detailed understanding of the vortex distribution law and energy losses under various working conditions. In this study, numerical simulations of a pump turbine model were conducted, and the results were consistent with the experimental results. The |ω|-criterion in the vortex analysis method was combined with the Q-criterion to reveal vortex distribution in the S-shaped region for each working condition along the Q11-n11 curve for all the conditions. Under the runaway and turbine break conditions, the flow field vortices were mainly the leaf channel vortex and separation vortex. Under zero-flow-rate and reverse-pump conditions, the vortices developed towards the stay-guide vanes, obstructing the flow path. Combined with the entropy production rate distribution, vorticity is closely related to energy loss. Compared to the rotation, the vorticity generated by the strong shear effect is significant.